The Effect of Religious Beliefs on the Attitude of Aesthetic Surgery Operation in Islam - Muslu, Ümran; Demir, Emre (2020)
This study aims to investigate the relationship between individuals’ attitudes about acceptance of aesthetic surgery (e.g. rhinoplasty, autoplasty, blepharoplasty, and mammaplasty) and some of the worship practices in Islamic religion such as performing prayer, fasting, and going to pilgrimage. Although many people think that aesthetic surgery is inappropriate in Islamic religion, no studies in the literature were found to have investigated this issue. This study collected data through a questionnaire administered to 96 patients who applied to our Plastic Surgery Clinic and underwent various surgical operations and 96 patients who were recommended plastic surgery but rejected to have one; the questionnaire aimed to identify the participants’ frequency of religious worship practices and appropriateness of aesthetic surgery to their beliefs. The participants responded on the frequency of religious worship levels according to the options in the questionnaire. The “Acceptance of Cosmetic Surgery Scale” was utilized in order to identify their attitudes towards aesthetic surgery. Levels of performing prayers, fasting, and going to pilgrimage in the groups that accepted surgery and in the groups that rejected surgery were significantly different (p < 0.001, p = 0.008, p < 0.001). In two different groups, the Acceptance of Aesthetic Surgery Scale scores were significantly different within the prayer groups and fasting groups (p < 0.001, p < 0.001, p = 0.001, p < 0.001). While the group that accepted surgery indicated no significant differences between those who thought about going to pilgrimage and who did not (p = 0.650), there was a significant difference in the group that rejected surgery (p < 0.001). While 14.6% of the participants in the group that accepted surgery considered aesthetic surgery a sin, this proportion was 56.3% in the group that rejected surgery, and this difference was significant (p < 0.001). In both surgery groups, there were differences in the scale scores of those who considered aesthetic surgery a sin and those who did not (p < 0.001, p < 0.001). There was a significant relationship between worship practices, one of the biggest indicators of the level of belief in Islamic religion, and aesthetic surgery attitudes. However, despite the fact that belief levels affect the decision of having an operation in plastic surgery, in case of serious health problems, the decision of having an operation becomes more important religious beliefs.
Keywords: Aesthetic surgery; cosmetic surgery; Islam; Religion